1996
DOI: 10.3109/02656739609023523
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II study to evaluate radiation therapy and hyperthermia for deep-seated tumours: A report of RTOG 89–08

Abstract: The purpose of this paper is to evaluate the safety and efficacy of deep hyperthermia in conjunction with radiation therapy. This study employed 'second generation' electromagnetic devices which were felt to be better able to confine heating and spare normal tissue than the devices evaluated in a previous study (RTOG 84-01). Sixty six patients at six institutions were enrolled on a prospective Phase I/II study. Eligible deep seated tumours were treated with a combination of external hyperthermia and radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…While the results with alkaline labile DNA damage were consistent with the observed changes in the survival curve parameters, the role of DNA damage per se (or its repair) in the radiosensitization by 41 as the result of unrepaired or misrepaired DNA damage 19 . Micronucleus induction (®gure 5(a)) for radiation alone, or for radiation after 1 h at 41.18C, i.e.…”
Section: Resultssupporting
confidence: 75%
“…While the results with alkaline labile DNA damage were consistent with the observed changes in the survival curve parameters, the role of DNA damage per se (or its repair) in the radiosensitization by 41 as the result of unrepaired or misrepaired DNA damage 19 . Micronucleus induction (®gure 5(a)) for radiation alone, or for radiation after 1 h at 41.18C, i.e.…”
Section: Resultssupporting
confidence: 75%
“…Hyperthermia treatments are usually combined with either chemotherapy or radiation treatments or, in some instances, with both treatment modalities. Numerous animal and clinical studies have demonstrated that combined radiation/hyperthermia treatments provide local control of cancer superior to that of radiation treatments alone, provided that the temperatures of all malignant tissues are raised to sufficiently high temperatures and maintained at these temperatures for sufficiently long durations [4], [5]. The safe implementation of these two seemingly simple requirements is, in practice, often very difficult because there are only narrow ranges of temperature duration that produce good therapeutic effects in malignant tissues without damaging healthy tissues.…”
Section: Hyperthermia Treatment Of Localized Prostate Cancermentioning
confidence: 99%
“…Despite several single institution and collaborative group eOE orts, the results to date have been disappointing (Emami et al 1991, Anscher et al 1992, Myerson et al 1996 due, at least in part, to the inability to produce therapeutic temperatures within the prostate gland. One strategy to overcome the limitations of external heating systems is transrectal hyperthermia.…”
Section: Introductionmentioning
confidence: 96%